TROLI BELANJA SEBAGAI KONSEP PERANCANGAN KURSI TERAS - Is Rizal Khoirul Anwar (SULUH: Jurnal Seni Desain Budaya, 2021)
Human needs are increasing, chairs and tables are one of the supporting factors for human activity, the design of a process to create products for humans in their activities, in creating products, a research approach is needed so that the products created are really needed. The design process is a long series of work to create a product, design covers all possible aspects to be solved by imagination and creativity, so that innovative products are created. Sketches are selected at the initial stage in the product process, work drawings as a reference for product work, system construction or the method used to strengthen the product, finishing increases the beauty value of wood grain, durability, friction and punch strength can add value to the product, creating a product needs to explore shape and adequate study and supported by complete data.